Kajian Tentang Komunitas Virtual: Kesempatan dan Tantangan Kajian di Bidang Ilmu Komunikasi - Anastasia Yuni Widyaningrum (Fakultas Ilmu Komunikasi UKWMS, 2021)
This article is a literature review on virtual communities from phenomena, theories to the application of methods and research opportunities and challenges. The Internet removes the constraints of space and time and allows individuals to be connected from multiple locations and across identities. Using Sociological thinking about gemeinschaft and gesselschaft to explain the existence of communities in the internet era called virtual communities, this literature review seeks to apply them in the study of Communication Science. Various studies on virtual communities have been driven by rapid development of social media which enable long distance communication among people living in the different places all over the world. Artikel ini merupakan kajian literatur mengenai komunitas virtual dari fenomena, teori hingga aplikasi metode dan peluang serta tantangan penelitian. Internet meniadakan kendala ruang dan waktu dan memungkinkan keterhubungan individu dari berbagai lokasi dan lintas identitas. Menggunakan pemikiran sosiologi tentang gemeinschaft dan gesselschaft untuk menjelaskan keberadaan komunitas di era internet yang disebut dengan komunitas virtual, kajian literatur ini berusaha untuk menerapkannya dalam kajian ilmu komunikasi. Berbagai kajian mengenai komunitas virtual muncul dikarenakan salah satunya perkembangan media sosial yang memungkinkan individu yang tersebar secara fisik berinteraksi di dunia maya.